Analysis of kinetic models for chalcopyrite flotation: effect of operating parameters. Issue 5 (3rd September 2019) - Asghari, Mehrshad; Salmani Nuri, Omid; Allahkarami, Ebrahim
ABSTRACT: In this research, the influence of pH, particle size, the type of collector and frother and their concentration was studied on the flotation kinetic parameters, rate constant and ultimate recovery. In this regard, three different kinetic flotation models such as Classical model, Klimpel model, and fully mixed reactor model were applied to evaluate the batch flotation results. The results showed that the fully mixed reactor model gave the best fit to the experimental data. In the second stage, variation of flotation rate constants and ultimate recoveries are investigated with respect to particle size and chemical conditions. It was found that the rate constant ( k ) and ultimate recovery ( R ∞ ) were strongly dependent on pH and types of collector and their frother and dosages. It was also observed that best values of R ∞, K, separation efficiency, and selectivity index are obtained in the presence of a mixture of isopropyl- n -ethyl thionocarbamate (C4132) and Flomin C7240 (a mixture of 10–20 wt% sodium alkyl dithiophosphate and 20–30 wt% sodium mercaptobenzothiozole) as the collector and a mixture of polypropylene glycol (A65) and methyl isobutyl carbinol as the frother and dosages of 40 g/ton for both reagents, respectively.